LITERATURE AS A TOOL FOR ENHANCING LANGUAGE SKILLS - Jumaniyazova Lobar Sirojiddin qizi (TADQIQOTLAR, 2025)
ABSTRACT        This  article  explores  the  pivotal  role  of  literature  in  enhancing  language  skills within  English  language  learning  contexts.  Drawing  upon  empirical  studies  and theoretical frameworks, it examines how literature facilitates vocabulary acquisition, grammatical competence, cultural awareness, and critical thinking. The integration of literature  into  language  education  not  only  enriches  linguistic  proficiency  but  also fosters intercultural understanding and cognitive development. Various pedagogical strategies,  such  as  literature  circles  and  digital  storytelling,  are  discussed  to demonstrate  the  effectiveness  of  literature-based  instruction.  The  article  further addresses challenges related to text selection and learner variability, offering practical recommendations for educators.